1975
DOI: 10.1042/bj1480505
|View full text |Cite
|
Sign up to set email alerts
|

Tricarboxylic acid-cycle and related enzymes in restricted facultative methylotrophs

Abstract: The isolation is described of pure cultures of three non-methane-utilizing methylotrophic bacteria which, together with the previously described Bacillus PM6, have a very limited range of growth substrates; these organisms are designated "restricted facultative' methylotrophs. Two of these isolates, W6A and W3A1, grow only on glucose out of 50 non-C1 compounds tested, whereas the third isolate S2A1 and Bacillus PM6 grow on betaine, glucose, gluconate, alanine, glutamate, citrate and nutrient agar, but not on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
45
0

Year Published

1975
1975
1985
1985

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 18 publications
4
45
0
Order By: Relevance
“…1). Weitzman & Jones (1968) found that Gram-negative bacteria could be divided into two groups depending on whether or not AMP relieved the NADH-mediated Colby & Zatman (1972, 1975 inhibition of their citrate synthase, and that this division followed established taxonomic divisions. In this respect, bcaterium 5B1 and Pseudomonas 3A2 resemble other bacteria of the Pseudomonadaceae, Azotobacteriaceae and Neisseriaceae but differ from bacteria of the Enterobacteriaceae.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1). Weitzman & Jones (1968) found that Gram-negative bacteria could be divided into two groups depending on whether or not AMP relieved the NADH-mediated Colby & Zatman (1972, 1975 inhibition of their citrate synthase, and that this division followed established taxonomic divisions. In this respect, bcaterium 5B1 and Pseudomonas 3A2 resemble other bacteria of the Pseudomonadaceae, Azotobacteriaceae and Neisseriaceae but differ from bacteria of the Enterobacteriaceae.…”
Section: Resultsmentioning
confidence: 99%
“…Organisms 4B6, C2AI, W3A1, 5B1, Pseudomonas 3A2 and Bacillus PM6 were grown in 8-litre batches ofmineral base E (Owens & Keddie, 1969), containing 0.2% trimethylamine hydrochloride and vitamins where required (Colby & Zatman, 1973, 1975. The culture vessels were as described by Colby & Zatman (1974), except that additional aeration was achieved by bubbling filtered air through the cultures by means of a glass tube immersed in the culture medium.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The enzyme from the restricted facultative methylotroph, bacterium W3A1 (Colby & Zatman, 1975), has been isolated and shown to have a mol.wt. of 147000 (Steenkamp & Mallinson, 1976) and to contain a single tetrameric iron-sulphur centre (Hill et al, 1977), as well as an unusual yellow chromophore (Steenkamp & Singer, 1976).…”
mentioning
confidence: 99%